Romina and Cristina: Two New Strawberry Cultivars with High Sensorial and Nutritional Values. (30th November 2016) - Capocasa, F.; Balducci, F.; Di Vittori, L.; Mazzoni, L.; Stewart, D.; Williams, S.; Hargreaves, R.; Bernardini, D.; Danesi, L.; Zhong, C-F.; Mezzetti, B.
ABSTRACT: The two cultivars (Romina and Cristina) recently released from the Marche Polytechnic University (Ancona, Italy) strawberry ( Fragaria × ananassa ) breeding program, show high adaptability to non-fumigated soil. Furthermore, 'Romina' showed very early ripening, conic or bi-conic fruit shape, good taste with high sweetness, high firmness and shelf life, and high vitamin C and folate contents. 'Cristina' showed very late ripening, high productivity, large fruit of conical shape, good taste, and high vitamin C and folate contents. The European Union patents of 'Romina' and 'Cristina' have been transferred to the United States, and nursery production has begun following United States rules to determine future market interest.